2011
DOI: 10.1007/s00705-011-1035-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the first Chinese porcine sapelovirus strain

Abstract: Investigations were carried out to identify the causative agent of acute diarrhea, respiratory distress, and polioencephalomyelitis of pigs on a swine farm in Shanghai, China. Samples from the affected animals were tested for viruses and bacteria that are known to cause similar symptoms in swine, and only porcine sapelovirus (PSV; designated as csh strain) was isolated. The presence of PSV was further confirmed by the specific cytopathic effects observed in susceptible cells and by the results of PCR and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 29 publications
4
107
0
Order By: Relevance
“…The length of the 3′ UTR in PSV is 82 nucleotides (strain V13, YC2011, KS04105, KS05151 and KS055217) although a shorter sequence (68 nucleotides) was described for the csh strain [20]. In a previous report [12], PSV strain V13 was predicted to include three stem-loop structures in the region of the 3′UTR using nine nucleotides of the terminal part of the 3D coding region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the 3′ UTR in PSV is 82 nucleotides (strain V13, YC2011, KS04105, KS05151 and KS055217) although a shorter sequence (68 nucleotides) was described for the csh strain [20]. In a previous report [12], PSV strain V13 was predicted to include three stem-loop structures in the region of the 3′UTR using nine nucleotides of the terminal part of the 3D coding region.…”
Section: Discussionmentioning
confidence: 99%
“…PSV infections have been associated with a wide spectrum of symptoms ranging from asymptomatic infection to clinical signs including diarrhea, pneumonia, polioencephalomyelitis, and reproductive disorders [19]–[20]. Although PSVs can be important pathogens because of their wide distribution and high prevalence [21][25], the near-complete genomic sequences of only three PSV strains have been reported previously; one from the U.K. (V13 strain) and two from China (csh and YC2011 strains).…”
Section: Introductionmentioning
confidence: 99%
“…The symptomatic disorders include diarrhoea, pneumonia, polioencephalomyelitis and reproductive disorders (Alexandersen et al , 2012; Huang et al , 1980; Lamont & Betts, 1960; Lan et al , 2011; Schock et al , 2014; Sibalin, 1963). Experimental studies have demonstrated a diverse range of clinical symptoms (Lamont & Betts, 1960; Lan et al , 2011; Sibalin, 1963; Yamanouchi et al , 1965). These differences largely depend on age, route of infection and strains inoculated (Alexander & Betts, 1967; Lamont & Betts, 1960; Lan et al , 2011; Sibalin, 1963; Yamanouchi et al , 1965).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the genus Sapelovirus consists of three species, porcine, simian, and avian (9). Porcine sapelovirus (PSV) is confirmed to replicate in the gastrointestinal epithelia that causes acute diarrhea, pneumonia, and polioencephalomyelitis in swine (3).…”
mentioning
confidence: 99%